Taxonomic revision of Paralaubuca (Cypriniformes, Xenocyprididae), a taxon seemingly in decline - Tangjitjaroen, Weerapongse; Randall, Zachary S.; Yang, Lei; Grudpan, Chaiwut; Page, Lawrence M. (Zootaxa, 2025)
Although eight species names are available for the Southeast Asian genus Paralaubuca, and four names currently are in use, morphological and molecular data support recognition of only three names as valid, P. typus Bleeker, 1864, P. harmandi Sauvage, 1883, and P. barroni Fowler, 1934. Paralaubuca harmandi is easily distinguished from P. typus and P. barroni by having more lateral-line scales (70–87 vs. 51–68), fewer branched anal-fin rays (usually 22–24 vs. usually 24–28), and more scales around the caudal peduncle (usually 26–33 vs. usually 20–26). Paralaubuca typus and P. barroni are morphologically similar but can be separated consistently by number of rakers on the first gill arch, with P. typus having 31–51, and P. barroni having 22–29. Paralaubuca harmandi and P. typus are also separated by a COI genetic p-distance of 6.86–8.79%; molecular data are not available for P. barroni. Paralaubuca typus and P. harmandi have been recorded from the Chao Phraya, Mekong, and Mae Klong River basins, but both species appear now to be absent from the Mae Klong basin, not having been recorded there since 1966. Paralaubuca harmandi appears to be extremely rare in the Mekong River basin, where it has been documented at only two localities and not recorded since 1968. Paralaubuca barroni is found only in the Mekong River basin and documented at only three localities.